Intersectional Feminist Criminology: A Critical Companion to Theory and Research - Michalsen, Venezia (University of California Press, 2025)
This pathbreaking book brings to bear a sweeping body of contemporary intersectional feminist work to disrupt the entire discipline of criminology. Women have been largely absent from criminological theory, research, policy, and practice. This fresh, conversational book critiques the field's dominant theories by analyzing gendered patterns of perpetration and victimization and challenging traditional criminological perspectives on characteristics such as race and queerness. Designed as a rebuttal to conventional criminology textbooks, the book mirrors standard course content through an intersectional feminist lens, offering students a valuable opportunity to question the field's underpinnings and forge a new path to understanding the true meaning of justice.   Organized in fourteen chapters, each chapter includes accessible learning aids for students: A review of how traditional criminology textbooks cover the topic Critical perspectives on the topic Critical thinking breaks Intersectional Feminist Criminology is a timely intervention and companion to the curriculum that helps to imagine a new world and ultimately lays out a clear abolitionist vision as an alternative to the American criminal legal system.
Keywords: dept.soc

A Cell of One’s Own? Incarceration and Other Turning Points in Women’s Journeys to Desistance - Michalsen, Venezia (International Journal of Offender Therapy and Comparative Criminology, 2019)
Research has shown the importance of turning points in desistance from criminal behavior. Using qualitative data from a sample of 100 formerly incarcerated mothers interviewed about their criminal behavior, this article explores their descriptions of transition moments and whether and how those moments affected their criminal behavior. The findings indicate that whereas parenting emerges as a turning point, the practical difficulties of reentry may reduce the impact of mothering on women’s desistance. More self-focused turning points, such as those due to incarceration, arrest, and sobriety appeared to be particularly important to the women’s desistance. This article emphasizes the need for research into the subjective and environmental factors that affect women’s desistance behaviors.
Keywords: dept.soc; peer-reviewed

Abolitionist Feminism as Prisons Close: Fighting the Racist and Misogynist Surveillance “Child Welfare” System - Michalsen, Venezia (The Prison Journal, 2019)
The global prison industrial complex was built on Black and brown women’s bodies. This economy will not voluntarily loosen its hold on the bodies that feed it. White carceral feminists traditionally encourage State punishment, while anti-carceral, intersectional feminism recognizes that it empowers an ineffective and racist system. In fact, it is built on the criminalization of women’s survival strategies, creating a “victimization to prison pipeline.” But prisons are not the root of the problem; rather, they are a manifestation of the over-policing of Black women’s bodies, poverty, and motherhood. Such State surveillance will continue unless we disrupt these powerful systems both inside and outside prisons.
Keywords: dept.soc; peer-reviewed

Intersectional feminist criminology: A critical companion to theory and research - Michalsen, Venezia (University of California Press, 2025)
This pathbreaking book brings to bear a sweeping body of contemporary intersectional feminist work to disrupt the entire discipline of criminology. Women have been largely absent from criminological theory, research, policy, and practice. This fresh, conversational book critiques the field's dominant theories by analyzing gendered patterns of perpetration and victimization and challenging traditional criminological perspectives on characteristics such as race and queerness. Designed as a rebuttal to conventional criminology textbooks, the book mirrors standard course content through an intersectional feminist lens, offering students a valuable opportunity to question the field's underpinnings and forge a new path to understanding the true meaning of justice. Organized in fourteen chapters, each chapter includes accessible learning aids for students: A review of how traditional criminology textbooks cover the topic. Critical perspectives on the topic. Critical thinking breaks. Intersectional Feminist Criminology is a timely intervention and companion to the curriculum that helps to imagine a new world and ultimately lays out a clear abolitionist vision as an alternative to the American criminal legal system. © 2025 by Venezia Michalsen. All rights reserved.
Keywords: dept.soc

Not All Women Are Mothers: Addressing the Invisibility of Women Under the Control of the Criminal Justice System Who Do Not Have Children - Michalsen, Venezia; Flavin, Jeanne (The Prison Journal, 2014)
Research has consistently shown that most women under the control of the criminal justice system are mothers. The robustness of this finding has been accompanied by a failure to consider the characteristics and needs of women without children. In this study, we examine data on 1,334 formerly incarcerated women. Findings indicate that while mothers and non-mothers share some characteristics, they differ on several others, most notably demographic profile, mental health, and timing of contacts with the criminal justice system. These results suggest a need to recognize the diversity among women offender groups, particularly when developing policies and programs need.
Keywords: dept.soc; peer-reviewed

More than Visiting Hours: Maintaining Ties Between Incarcerated Mothers and Their Children - Michalsen, Venezia; Flavin, Jeanne; Krupat, Tanya (Sociology Compass, 2010)
The majority of people in America’s prisons are the parents of minor children. Incarcerated mothers, in particular, were likely to have been a part of their children’s lives before their imprisonment, and most will soon be returning to the community and to their children. Research has shown that it is in the best interests of the mothers and the children to maintain a relationship across the prison bars. In this article, we use the example of New York State to show how institutional policies and structures can impede or encourage efforts to maintain ties between women and their children and why demonstrating support for family ties must extend well beyond having visiting hours.
Keywords: dept.soc; peer-reviewed

Positive Mood and the Perception of Variability Within and Between Groups - Stroessner, Steven J.; Mackie, Diane M.; Michalsen, Venezia (Group Processes & Intergroup Relations, 2005)
Three experiments investigated the effects of positive mood on perceptions of variability within and between groups. Participants formed impressions of two different and highly variable groups under a neutral or positive mood. When participants expected to learn about both groups, positive mood increased perceived intergroup similarity but did not affect perceived intragroup variability. In contrast, when participants expected to learn about only one group, judgments of intergroup and intragroup similarity were both affected by mood. Mood and the intergroup context influenced the nature and degree of information processing and resultant judgments of variability in social groups.
Keywords: dept.soc; peer-reviewed